Effect of modified Traditional Chinese Medicine hot compress technique in the treatment of osteoarthritis of the knee (改良式中药热敷技术治疗膝骨关节炎效果观察) - CUI Yangfang (崔杨芳); LIU Ai (刘爱); ZHANG Xuejian (张雪键); ZHAO Yue (赵月); QI Mengying (齐梦颖) (中西医结合护理)
Objective To observe the effect of modified Traditional Chinese Medicine (TCM) hot compress technique in the treatment of osteoarthritis of the knee. Methods Totally 60 patients with osteoarthritis of the knee were randomly divided into the observation group and control group, with 30 cases in each group. The control group received conventional TCM hot compress technique, and the observation group received the modified hot compress technique by optimizing the size of Chinese herbal medicine package, regulating duration of treatment, and monitoring the temperature with electric temperature controller. Visual Analogue Scale was used to measure the pain, and Lysholm knee scale was used to measure the function of affected knee joint. The clinical effective rate and incidence of nursing adverse events were compared between two groups. Results The VAS score in the observation group was lower than that in the control group (P＜0. 01), The incidence of scalds in the observation group was lower than that in the control group (P＜0. 05). There was no significant difference in Lysholm knee scale and treatment efficacy between two groups (P＞0. 05). Conclusion Modified TCM hot compress technique has a remarkable curative effect in the treatment of knee osteoarthritis, which can relieve pain and improve the function of knee joint, and it is a safe technique in clinical practice . (目的 观察改良式中药热敷技术治疗膝骨关节炎的效果。方法 选取科室所收治的膝骨关节患者60例为研究对象, 采用随机数字法分为观察组和对照组, 各30例。对照组采用常规中药热敷治疗, 观察组在常规热敷治疗基础上, 改良中药药包的外形尺寸、治疗时间, 并应用电子温控仪进行恒定温度控制药包温度。采用VAS评分评估疼痛程度, 采用 Lysholm 膝关节功能评分评估患膝功能, 对比两组干预效果, 记录不良事件发生情况。结果 干预后观察组VAS评分改善优于对照组(P＜0. 01), 烫伤发生率低于对照组(P＜0. 05); 两组Lysholm 膝关节功能评分和临床疗效评价差异无统计学意义(P＞0. 05)。结论 改良式中药热敷技术治疗膝骨关节炎疗效明确, 能有效缓解疼痛, 改善膝关节功能, 提升中医治疗和护理安全性。)